Taxes to red and processed meat to promote sustainable and healthy diets in Mexico - Kaela Connors; Juan A. Rivera; Peter Alexander; Lindsay M. Jaacks; Carolina Batis; Dalia Stern; Martín Lajous; M. Arantxa Colchero (PLoS ONE, 2025)
Background Consumption of red and processed meat is above sustainable and healthy dietary targets in Mexico. Policies to promote greater adherence such as taxing meat are needed to reduce consumption. Here, we evaluated how price increases to red and processed meat could shift consumption for meat as well as other key food groups. Methods Using data from the Mexican National Household Income and Expenditure Survey (2018, 2020, 2022), we estimated own- and cross-price elasticities of demand for 10 food groups. These were used to predict changes in quantity demanded of each food group according to price increase scenarios. Results Price increases to meat increased demand for substitutes such as fruits and vegetables, legumes, poultry, and seafood, and reduced demand for salty snacks, sweets and sugary beverages. Substantial increases to the price of processed meat markedly reduced processed meat consumption, increased consumption of protein- and nutrient-rich foods, and resulted in more modest levels of red meat consumption. Lower-income groups were more sensitive to price increases but still met dietary recommendations for meat and substituted these foods with alternatives such as legumes and seafood. Conclusions Increasing the price of red and processed meat through a tax may promote greater adherence to sustainable and healthy dietary targets in Mexico. It simultaneously increased demand for healthier substitutes, and reduced demand for unhealthy complements. Substantially raising the price of processed meat only may be an effective strategy for addressing diet-related risk factors, while delivering environmental benefits. Additionally, meat taxes have the potential to promote improvements in diet quality and equitable health outcomes.